2020
DOI: 10.3390/app10113696
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematic Model of the Shoulder Complex Obtained from a Wearable Detection System

Abstract: Due to the complex coupled motion of the shoulder mechanism, the design of the guiding movement rules of rehabilitation robots generally lacks specific motion coupling information between the glenohumeral (GH) joint center and humeral elevation angle. This study focuses on establishing a kinematic model of the shoulder complex obtained from a wearable detection system, which can describe the specific motion coupling relationship between the GH joint center displacement variable quantity relative to the thorax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recent study found that the end-effector type ULRR intervention is better than the exoskeleton type ULRR intervention with regard to activity and participation among chronic stroke patients with moderate-to-severe impairment of upper extremity function after four weeks of intervention [ 9 ]. In addition, research studies have shown that the shoulder complex of upper limb is very complex, and it is difficult to design an exoskeleton type ULRR that is compatible with the upper limb of users because the glenohumeral joint moves with the functional relevance of the shoulder girdle during humeral elevation and the glenohumeral joint has three degrees of freedom (DOFs) with axes intersecting perpendicularly in the glenohumeral joint center, which is obviously a spherical joint and can be regarded with a generalized glenohumeral joint with floating center [ 7 , 33 ]. Also, the end-effector type ULRRs focus more on the rehabilitation of the combined motion of upper limb chain and assist the patient to perform collaborative tasks; they are safer compared with exoskeletons because they are not in direct contact with the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study found that the end-effector type ULRR intervention is better than the exoskeleton type ULRR intervention with regard to activity and participation among chronic stroke patients with moderate-to-severe impairment of upper extremity function after four weeks of intervention [ 9 ]. In addition, research studies have shown that the shoulder complex of upper limb is very complex, and it is difficult to design an exoskeleton type ULRR that is compatible with the upper limb of users because the glenohumeral joint moves with the functional relevance of the shoulder girdle during humeral elevation and the glenohumeral joint has three degrees of freedom (DOFs) with axes intersecting perpendicularly in the glenohumeral joint center, which is obviously a spherical joint and can be regarded with a generalized glenohumeral joint with floating center [ 7 , 33 ]. Also, the end-effector type ULRRs focus more on the rehabilitation of the combined motion of upper limb chain and assist the patient to perform collaborative tasks; they are safer compared with exoskeletons because they are not in direct contact with the human body.…”
Section: Introductionmentioning
confidence: 99%